?PHYSICO-CHEMICAL STUDIES OF EFFLUENTS_AND EMISSIONS OF GHEEIEDIBLE OIL INDUSTRIES IN PAKISTAN - Ahmad, Irshad; Ali, Saqib; Jane, M Rasool (Biological Sciences - PJSIR, 1999)
Samples of the effluents from various Ghee I Edible Oil Industries were collected on fortnightly basis from July 1993 to June 1994 and of the emissions from January to April 1994. Parameters such as temperature, pH, conductivity, total dissolved solids (TDS), total suspended solids (TSS), total alkalinity I total acidity, total hardness, chemical oxygen demand (COD), chlorides, sulphates, phosphates, silica, calcium, magnesium, sodium, and iron were determined in the effluents. Trace metals like copper, manganese, nickel, and zinc were determined by atomic absorption spectros- copy, whereas S02’ CO CO2, hydrocarbons, hydrogen, nitrogen, oxygen and argon were examined in the flue gases by Gas Chromatography and other standard techniques such as Orsat Gas Analyzer and Dragger Detection Tubes. Remedial measures were suggested for the pollutants exceeding the National Environmental Quality Standards, (NEQS). Parameters like chlorine" ammonia, sulphides, arsenic,cadmium, chromium, cobalt, lead and tin were also analyzed in the effluents and were found to be nil or below the detection limit, while particulate matters, HCr, chlorine, HF, H2S, mercaptans and NH3 were found to be nil in the flue gases.